Maternal and child health care practice of Tamang community - Timalsina, Suresh (Innovative Research Journal, 2022)
Health is the most important factor of human life. It is a multi-dimensional process and a quality of life which entails a dynamic interact among the physical, mental, social, emotional and spiritual aspects of life. Good health improves the quality of life. The major health problems of Nepal are highly related to maternal and child health care practices. So, MCH care is the very important component of primary health care in Nepal. Most of the women of Nepal are illiterate and ignorant regarding the high maternal and child mortality rate in Nepal. This research was based on descriptive research design with both quantitative and qualitative nature of information. The major results from the findings of this study reveals that 29.5 percent respondents had not antenatal checked up and 70.4 percent respondents had antenatal checked up. The majority of the respondent (34.1 percent) women had antenatal checked up of three times during pregnancy period, whereas 38 percent of the pregnant women had checked up for four times, few (6.9 percent) of the pregnant women had five times antenatal checked up during pregnancy period. It was found that majority of the respondents (63.6 percent) had antenatal checked in health post and most of the respondent’s (64.8 percent) first child bearing age was found to be 15-19 years of age and least of the (4.5 percent) respondent’s first child bearing age was found 25-29 years of age. Similarly, 47.7 percent of respondent mothers had taken one dose of TT injection and 31.9 percent of respondent mothers had taken non dose of TT injection.